Implementación del Diplomado en Gestión Integrada de Recursos de Agua en el Perú - Floris, Vinio (2019)
The Consortium led by GERNS Postgraduate School (Peru) and its partners, Colorado State University (USA) and Fundación Chile (Chile), designed and implemented a Graduate Diploma Program on Integrated Water Resources Management for Mid-career professionals in Peru during 2014-2015. It was oered to over a hundred regional and local professionals from several institutions that belong to the National Water Resources Management System as part of the Modernizationof the Water Resources Management Program of the National Water Resources Authority (ANA). The Graduate Diploma Program had a signicant impact on its participants and organizations based on the positive comments of the actors involved: students, sponsoring organizations and instructors. Considerable improvements have been observed in the decisionmaking- process, progress in the holistic approach of water resources management, and a bolstering of the professional careers of the participants.